(untitled) (Zia e Tahqeeq, 2025)
Shah Waliullah is the leading scholar of 18th century who is famous for his revivalist and Ijtihadi ideas. He played a vital role in harmonizing the conflicting trends of various sects. In order to achieve the target, he composed many books and commentaries. For instance, he wrote al-Masawwa –a commentary on al-Mutta to make conformity between Hanafi and the Shafi’i jurisprudential differences. Later on, he wrote Musaffa- another commentary on al- Mutta to create ways of proximity among four famous schools of thoughts. His writings reflect his Ijtihadi approach. He also criticized taqlid or blind following or imitation. It is necessary to understand the definition and limitation of taqlid in the in his theory. This article attempts to evaluate Shah Waliullah’s theory of Taqleed. In this article, some issues also are discussed in which jurisprudential differences exist since the early period of Islam. The present study also contains that for whom imitation is forbidden in the theory of Shah Waliullah. This research helps to determine the nature of Shah Waliullah theory of Taqlid.